Uncomfortable User Experience. - BENFORD, STEVE; GREENHALGH, CHRIS; GIANNACHI, GABRIELLA; WALKER, BRENDAN; MARSHALL, JOE; RODDEN, TOM (Communications of the ACM, 2013)
The article discusses the engineering of discomfort as a means to engage computer user experience by integrating perspectives from human-computer interaction and performance studies. Topics covered include a way for designers to employ visceral and cultural discomfort, effects of uncomfortable interaction on users, the involvement of a tradition of discomfort in the arts, the prototype amusement park ride called Breathless and the primary forms of discomfort, It also discusses ethical challenges posed by discomfort.